PROBLEMS OF CREATING A ROBOT EYE ANALYZER SYSTEM FOR HUMAN FACE RECOGNITION AND IDENTIFICATION - Davranova Motabar Abror qizi (Ecominds Press, 2025)
In this paper, sufficient scientific research on identifing the similarities of two images has been conducted, and information on the availability of sufficient algorithms and software products in this area has been provided. The recognition algorithm consists of comparing two images and determining their similarity. The authors have developed a comprehensive analysis of existing algorithms for the recognition process, taking into account their capabilities and shortcomings. A new criterion, algorithm and software are developed for the recognition process, as well as the examples showing its performance and high level of accuracy has been proved.
Keywords: Coefficient, correlation identification, face images, features, methods, statistics.